Price and quality in spatial competition - Brekke, Kurt R. (2010)
We study the relationship between competition and quality within a spatial competition framework where firms compete in prices and quality. We generalise existing literature on spatial price–quality competition along several dimensions, including utility functions that are non-linear in income and cost functions that are non-separable in output and quality. Our main message is that the scope for a positive relationship between competition and quality is underestimated in the existing literature. If we allow for income effects by assuming that utility is strictly concave in income, we find that lower transportation costs always lead to higher quality. The presence of income effects might also reverse a previously reported negative relationship between the number of firms and equilibrium quality. This reversal result is further strengthened if there are cost substitutabilities between output and quality. Equilibrium quality provision is always less than socially optimal in the presence of income effects.